Dialectics and Logics in Forensic Enquiry of Construction Facilities - BUTYRIN, Andrey Yurievich; STATIVA, Ekaterina Borisovna (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The main goal of this article is to develop measures related to ensuring harmonic development of scientific and methodological, and conceptual and categorical frameworks of the construction expert. Based on the results of generalization and analysis of the practice of forensic and construction and technical enquiry, the authors state inadmissible informality of its scientific and methodological basis. It was expressed in the lack of dialectics and logics as integral elements of cognition in the range of the forensic construction expert’s research tools. The work clearly demonstrates the possibility of direct application of dialectics laws and logics methods as the basis of solving practical tasks set by the investigator or the court to experts. Dialectics and logics are here represented as obligatory tools of the legal expert cognition process and defining objective circumstances of the criminal or civil case. This is the first time when high philosophical categories are integrated in the conceptual and categorical framework of the construction facilities researcher that was priory represented only by means of the technical language. According to the authors, such approach will provide structural improvement and intuitive completeness of the system of special construction and technical knowledge that are more and more needed by the modern court proceedings.
Keywords: forensic construction and technical enquiry; methodological apparatus; conceptual and categorical framework; dialectics laws; logic methods; reasons of incidents of construction facilities